Legal Protection for Foreign Lenders in Indonesia's Peer-to-Peer Lending Market: Borrower Default Risk under the LPBBTI Framework - Fika Pratiwi; I Made Sarjana (IJBLE Scientific Publications Community Inc., 2026)
Indonesia's technology-based joint funding service (Layanan Pendanaan Bersama Berbasis Teknologi Informasi, LPBBTI) has become an important channel of digital credit, while simultaneously exposing fund providers to borrower-default, platform, operational, and enforcement risks. This article examines the legal position and protection of foreign parties that provide funds through Indonesian LPBBTI platforms, with particular attention to borrower default. It uses normative doctrinal legal research, combining statutory and conceptual approaches and examining the Indonesian Civil Code, the investment framework, financial-sector legislation, OJK Regulation No. 40 of 2024, OJK Circular Letter No. 19/SEOJK.06/2025, and relevant legal and fintech scholarship. The analysis makes a distinction that is often blurred in Indonesian discussion: a foreign lender who supplies funds to a borrower through an LPBBTI platform is not legally identical to a foreign equity investor who owns shares in the platform operator. This distinction changes the applicable rights, obligations, regulatory limits, and remedies. The article finds that legal protection is layered. Preventive protection rests on licensing, risk disclosure, credit scoring, funding-performance transparency, contractual risk allocation, portfolio diversification, data governance, and prudential platform conduct. Repressive protection arises through contractual claims, default remedies, dispute resolution, and platform liability where loss is attributable to the operator's own breach or negligence. The regulatory framework provides substantial legal certainty, but it does not guarantee repayment and should be strengthened through clearer cross-border contractual clauses, standardized disclosures, and continuity arrangements for distressed platforms.